The Malaysian public sector training program evaluation : a fact or fallacy : a Ministry of Defence case study (Table of contents and abstract only) - Subhas, Chandran (2006)
The MINDEF Corporate Plan identifies development of human capital as one of the thrusts for implementation. Conseq~~enttlhye MINDEF allocates about RM 92.7 million annually for training and development of capability. This accounts for about 12% of the yearly MINDEF Operating Expenditure (OE) Budget for the year 2006. On a training dollar per head basis spent on trainees, MINDEF has committed to expend about RM 22,524 / head (trainee) to ensure that the Armed Forces maintain their cutting edge in defense capability. The program agreement that is entered into by the program manager (implementer) and the controlling officer (financier) requires that programs be evaluated for program appropriateness, effectiveness, efficiency, economy and value for money in resource usage. Evaluation based on these criteria, it is expected, will allow program managers the ability to establish the program impact. (Author's abstract)